Utility of HS-CRP as an add on to Lipid Profile for Cardiovascular Risk Stratification in Adults with Type II Diabetes Mellitus - Iqtidar-Ud-Din, Tayyaba Batool, Syed Hyder Raza, Alard Yasir, Rizwan Abdul Salam, Nasreen Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus (DM), which has a significant mortality and morbidity percentage, has emerged as a major health hazard. The aim of this study to evaluate the effects of hs-CRP with lipid profile effects on CVS risk in type II diabetic patients. Study design: It was a cross-sectional study conducted in the People’s University of Medical and Health Sciences for Women, Nawabshah, for six month duration from March 2022 to August 2022. Methodology: The total participants were 250 which included 180 diabetic participants and other remaining 70 were non-diabetic participants. These participants were divided into two groups, one group was non-diabetic participants serve as control group and other was diabetic group. The data analyses were done by SPSS 21 version. Results: The mean age of the male and female participant was 50.5±9.9 and 49.48±10.5. There was no significance change in the demographic variables like BMI, weight, systolic pressure and diastolic pressure p>0.005 in diabetic and control group. The participants were 31% and 72% raised CVS risk due to increase of LDL and hsCRP levels. The LDL, TC and TG were statistically significant in the participants having >4 mg/dl of hs-CRP. The HDL and ratio of HDL/LDL level were reduced significantly having >4 hs-CRP mg/dl. Conclusion: According to our observations, patients who are diabetic participants commonly have raised hs-CRP levels along with dyslipidemia. Continuous monitoring of these indicators can sometimes support in reducing the CVS risk among patients. Keywords: lipid profile, dyslipidemia, significant mortality and morbidity.